Sampah Plastik Menjadi Briket Sebagai Bahan Bakar Alternatif Dengan Penambahan Paper Waste - Hamzah, Mat (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2019)
ABSTRAK Making briquettes from plastic waste and paper waste can make briquettes as an alternative uel . The purpose of this study was to find out how the resulting heat value produced from plastic waste briquettes through fuel test. The plastic waste obtained is burned to form. Plastic in the form of further granules mixed with 10% starch 1:1 dan 2:1 (plastic waste : paper waste). The material is printed using a mineral cup, then dried under the sun for three day. The calorific value produced from plastic waste briquettes through cooking water as much as 200 gram produces 60-62 oC heat. Keywords : fuel test, paper waste, plastic briquettes starch, plastic waste